UTILIZATION OF JAMU IN PUERPERAL MOTHER IN SUMATERA AND JAVA ISLAND (LITERATURE REVIEW OF HEALTH ETHNOGRAPHIC RESEARCH 2012-2016) - Zulfa Auliyati Agustina; Yunita Fitrianti (Universitas Airlangga, 2020)
ABSTRACTIndonesian people used to consume herbal medicines called